Abnormalities of hippocampal shape and subfield volumes in medication‐free patients with obsessive–compulsive disorder. Issue 14 (12th June 2019) - Zhang, Lianqing; Hu, Xinyu; Lu, Lu; Li, Bin; Hu, Xiaoxiao; Bu, Xuan; Li, Hailong; Tang, Shi; Yang, Yanchun; Roberts, Neil; Sweeney, John A.; Gong, Qiyong; et al.
Abstract: In this study, we sought to identify alterations of hippocampal shape and subfield volumes in a relatively large sample of medication‐free obsessive–compulsive disorder (OCD) patients without comorbid depression. 3D T1‐weighted Magnetic Resonance Imaging scans were collected from 81 medication‐free OCD patients and 95 age‐ and sex‐matched healthy controls (HC). Total hippocampal volume and volume of eight bilateral subfields were measured using FreeSurfer software. Subregional shape deformity was examined via FSL software. Volumetric and shape differences between groups and correlations with OCD symptoms were examined. The volume of right hippocampus was significantly reduced in OCD patients ( p = .001, η 2 = 0.065). Follow‐up analysis of right hemisphere subfields showed reduced volume in right subiculum ( p  < .001, η 2 = 0.081), presubiculum ( p  < .001, η 2 = 0.125), CA2/3 ( p = .001, η 2 = 0.06), and hippocampal tail ( p  < 0.001, η 2 = 0.105), while the volume of right fimbria was increased ( p = .001, η 2 = 0.058). Shape analysis revealed a bilateral outward bending in the hippocampal body related to a lateral displacement of hippocampus from the body to the tail. Symptom severity was correlated with volumes of presubiculum (with compulsions, r = −0.25, p = .024) and fimbria (with obsessions, r = −0.28, p = .012), and with the lateral shift of middle and posterior hippocampus (with obsessions). Alterations across hippocampal subfields and overall shape may contribute to the distinctive cognitive and affective abnormalities associated with OCD.